Penggunaan Media Civic Dart Berbasis Game Edukatif sebagai Upaya Meningkatkan Keaktifan Pembelajaran Pendidikan Pancasila pada Murid Kelas X TKR SMKN - Suhari Suhari; Alif Bima Kusuma; Aprilia Indi Prastika; Hanifah Agustina; Lennin Kartika Eka Santosa Putri; Vemy Indah Sari; Yusuf Setyoko (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: The low level of student engagement in Pancasila Education learning in Class X TKR at SMKN serves as the background of this study, with only 25–30% of students actively participating. This study aims to describe the implementation, analyze the improvement in student engagement, and identify the supporting and inhibiting factors in the use of Civic Dart media based on educational games. A qualitative case study approach was employed, involving 36 students as research subjects. Data were collected through observation, in-depth interviews, and documentation, and subsequently analyzed using the interactive model proposed by (Miles et al., 2014). The findings indicate that implementation proceeded systematically across three phases and elicited positive responses from students. Student learning engagement increased significantly from 28.3% to 72.5%, particularly in the verbal, mental, and emotional dimensions. Supporting factors included institutional support and teacher openness, while inhibiting factors encompassed time management constraints and participation disparity among students. It is concluded that Civic Dart is effective in enhancing student engagement in Pancasila Education learning at the vocational secondary school level.Abstrak: Rendahnya keaktifan murid dalam pembelajaran Pendidikan Pancasila di kelas X TKR SMKN menjadi latar belakang penelitian ini, dengan hanya 25-30% murid yang aktif berpartisipasi. Penelitian bertujuan mendeskripsikan implementasi, menganalisis peningkatan keaktifan, dan mengidentifikasi faktor pendukung serta penghambat penggunaan media Civic Dart berbasis game edukatif. Pendekatan kualitatif studi kasus digunakan dengan 36 murid sebagai subjek. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, lalu dianalisis menggunakan model interaktif (Miles et al., 2014). Hasil penelitian menunjukkan implementasi berlangsung sistematis melalui tiga fase dengan respons positif. Keaktifan belajar meningkat signifikan dari 28,3% menjadi 72,5%, terutama pada dimensi lisan, mental, dan emosional. Faktor pendukung meliputi dukungan institusional dan keterbukaan guru, sedangkan faktor penghambat mencakup manajemen waktu dan disparitas partisipasi. Disimpulkan bahwa Civic Dart efektif meningkatkan keaktifan pembelajaran Pendidikan Pancasila di SMK.